Online-Based Sexual Harassment - Safaruddin Harefa (The Easta Journal Law and Human Rights, 2022)
Social media interactions with other people's different behaviors can include sexual harassment, intimidation, fraud, and more. The rapid development of technology is like a double-edged sword, which not only has a positive impact but also a number of negative impacts. According to Dowdell (2011), the easiest way for today's perpetrators to meet a child or teenager and plunge them into sexual harassment, pornography, or prostitution is through the Internet. Its form can be in the form of speech, writing, symbols, search, and semantic movement. The type of research in this study is normative juridical which means . Meanwhile, according to Collier (1998), the concept of sexual harassment is any form of unwanted sexual behavior, sexual harassment that can occur or be experienced by all women who receive treatment. Meanwhile, according to Rubinstein (in Collier, 1998), sexual harassment is the unwanted nature of sexual behavior or gender-based actions that offend the recipient. Types of sexual harassment, technology-based sexual violence, dissemination of sexual content, gender-based violence (KBG) and sexual blackmail